Antioxidant Potential of Raw Meat from Broiler Chicken Fed with Dietary Plant Supplements - Upadhyay, Atul; Katuwal, Nirat; Rai, Basanta Kumar; Shrestha, Srijan; Bhattarai, Rewati; Makise, Tadahiro (Himalayan Journal of Science and Technology, 2017)
Abstract available on the full text PDF.